A NOVEL, SIMPLE, RAPID RP-HPLC METHOD FOR SIMULTANEOUS ESTIMATION OF FERULIC ACID, QUERCETIN, PIPERINE AND THYMOL IN AYURVEDIC FORMULATION - SHAIKH, HEENA A. R.; Jain, Vandana (International Journal of Applied Pharmaceutics, 2018)
Objective: A simple, accurate, precise and robust reverse phase high performance liquid chromatography (RP-HPLC) method was developed for simultaneous estimation of ferulic acid, quercetin, piperine and thymol in marketed ayurvedic formulation. Methods: The selected markers were resolved using shim pack GIST C-18 column, with mobile phase acetonitrile: 0.04 M potassium dihydrogen ortho phosphate buffer (pH 3.0 adjusted with ortho phosphoric acid) in a ratio of 60:40 v/v at a flow rate of 1.0 ml/min. The detection was carried out at 264 nm. Results: The retention time of ferulic acid, quercetin, piperine and thymol were found to be 2.98, 3.35, 7.83 and 9.72 min respectively. The developed method was validated according to the guidelines provided in ICH Q2 (R1) in term of linearity, precision, limit of detection, limit of quantification, accuracy and robustness. Linear response for all selected markers was obtained in the concentration range of 12-28 Âµg/ml with a correlation coefficient (r2) greater than 0.999. The mean % recovery was found to be 99.30 for ferulic acid, 98.77 for quercetin, 100.93 for piperine and 100.25 for thymol. Conclusion: The developed method was applied for quantification of these marker in marketed ayurvedic formulation. This method can be used to evaluate other formulations containing these selected phytoconstituent, thus conforming the quality and safety of ayurvedic or polyherbal formulations.